2021
DOI: 10.1038/s41467-021-21998-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and targets of Fcγ-receptor mediated immunity to malaria sporozoites

Abstract: A highly protective vaccine will greatly facilitate achieving and sustaining malaria elimination. Understanding mechanisms of antibody-mediated immunity is crucial for developing vaccines with high efficacy. Here, we identify key roles in humoral immunity for Fcγ-receptor (FcγR) interactions and opsonic phagocytosis of sporozoites. We identify a major role for neutrophils in mediating phagocytic clearance of sporozoites in peripheral blood, whereas monocytes contribute a minor role. Antibodies also promote nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(109 citation statements)
references
References 63 publications
12
97
0
Order By: Relevance
“…This association was observed in two independent experiments using both the PBLs and highly purified (>99%) neutrophils. These findings corroborate a recent study that showed that neutrophil opsonic phagocytosis of sporozoites is important in malaria immunity and suggest that the role of neutrophils in controlling parasitemia may transcend different stages of the parasite 18 . Since the PBL-phagocytosis assay developed here measures the phagocytic activity of all leukocytes, our analysis also demonstrated that the phagocytosis promoting activity of monocytes was significantly associated with a reduced risk of febrile malaria in this Ghanaian cohort.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This association was observed in two independent experiments using both the PBLs and highly purified (>99%) neutrophils. These findings corroborate a recent study that showed that neutrophil opsonic phagocytosis of sporozoites is important in malaria immunity and suggest that the role of neutrophils in controlling parasitemia may transcend different stages of the parasite 18 . Since the PBL-phagocytosis assay developed here measures the phagocytic activity of all leukocytes, our analysis also demonstrated that the phagocytosis promoting activity of monocytes was significantly associated with a reduced risk of febrile malaria in this Ghanaian cohort.…”
Section: Discussionsupporting
confidence: 91%
“…While the role of monocytes in NAI against malaria is well established 12 14 , 23 , we show here that antibody-mediated phagocytosis of blood-stage P. falciparum by neutrophils is also involved in NAI. Due to their greater numbers, we predict that neutrophils are the main effector cells that control blood-stage malaria parasite multiplication in vivo a notion, which may also hold true for pre-erythrocytic stage infections 18 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The lack of boosting for the vaccine-induced anti-CSP IgG Abs by the continuous natural exposure might be explained by the slow acquisition of pre-erythrocytic immunity in children [18]. Furthermore, there were no measurable levels of anti-CSP IgG among the controls, suggesting that natural P. falciparum infection does not induce substantial quantities of anti-CSP IgG specific memory B cells in children.…”
Section: Discussionmentioning
confidence: 98%
“…We also examined antibody responses to the specific regions of CSP using several antigen constructs. These included synthetic peptides representing the N-terminal region between amino acids 19-104 (NT) ( 38 ) and the central-repeat region comprised of the NANP motif repeated 15 times (NANP), both synthesized and purified by Life Tein (USA). We also used a recombinant protein representing the C-terminal region between amino acids 237-383 (CT) and a truncated CSP that lacked the central-repeat region (N+C), both expressed in HEK293 cells as previously described ( 23 , 38 ).…”
Section: Methodsmentioning
confidence: 99%